ANALISIS PERBEDAAN FENOMENA SHORT-TERM UNDERPRICING DAN LONG-TERM UNDERPERFORMANCE PADA SAHAM PERUSAHAAN BUMN DAN BUMS YANG MELAKUKAN IPO DI BEI TAHUN 2000–2010 - Indira Rully Widhawati; Yunia Panjaitan (Fakultas Ekonomi dan Bisnis Universitas Katolik Indonesia Atma Jaya, 2014)
The research is intended to analyze short term underpricing and long term underperformance on state and private company shares. Samples used are 11 state company share and 97 private sector share which experienced short term underpricing with average first day return method plus 7 state company shares and 91 state company shares which had long term underperformance using 3 years buy and hold method and wealth relative. By using different test non parametric Mann-Whitney U is concluded that private sectors shares has higher underpricing level which give benefit to short term investor. While State company shares has better performance on long term with WR level reaching 1 compared to private sector shares.